Analisis Kelayakan Investasi Pemasangan Sensor Level Pada Clearator Tank PDAM Surya Sembada Surabaya - Farahdiansari, Ardana Putri; Anggraeni, Wina (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The occurrence of problems in the production process is something that must be resolved immediately so it to disrupt the smooth protracted production process, as is the case with process disturbances that occur in the clean water production process at PDAM Surya Sembada Surabaya. In the process of water flow being processed from the filter tank to the clearator tank, water overflow often occurs due to a sudden increase in water discharge without monitoring. As a result of this overflow of water, production materials are wasted and of course also results in wasted costs. This problem was tried to be solved by installing a level sensor on the tank clearator so that the water level could be monitored by the monitoring team. Warning when the water level approaches the threshold will help the operator to immediately reduce the water discharge coming out of the tank filter so that there is no wasted overflow of water. Feasibility analysis of investing in the installation of level sensors carried out to find out for sure whether from an economic point of view this level sensor provides benefits for the company. By calculating the Net Present Value (NPV) and Benefit Cost Ratio (BCR), it will be known how the investment feasibility of installing the level sensor.